Modeling riboflavin transporter deficiency type 2: from iPSC-derived motoneurons to iPSC-derived astrocytes - Magliocca, Valentina; Lanciotti, Angela; Ambrosini, Elena; Travaglini, Lorena; D’Ezio, Veronica; D’Oria, Valentina; Petrini, Stefania; Catteruccia, Michela; Massey, Keith; Tartaglia, Marco; Bertini, Enrico; Persichini, Tiziana; et al. (Frontiers in Cellular Neuroscience, 2024)
Riboflavin transporter deficiency type 2 (RTD2) is a rare neurodegenerative autosomal recessive disease caused by mutations in the SLC52A2 gene encoding the riboflavin transporters, RFVT2. Riboflavin (Rf) is the precursor of FAD (flavin adenine dinucleotide) and FMN (flavin mononucleotide), which are involved in different redox reactions, including the energetic metabolism processes occurring in mitochondria. To date, human induced pluripotent stem cells (iPSCs) have given the opportunity to characterize RTD2 motoneurons, which reflect the most affected cell type. Previous works have demonstrated mitochondrial and peroxisomal altered energy metabolism as well as cytoskeletal derangement in RTD2 iPSCs and iPSC-derived motoneurons. So far, no attention has been dedicated to astrocytes. Here, we demonstrate that in vitro differentiation of astrocytes, which guarantee trophic and metabolic support to neurons, from RTD2 iPSCs is not compromised. These cells do not exhibit evident morphological differences nor significant changes in the survival rate when compared to astrocytes derived from iPSCs of healthy individuals. These findings indicate that differently from what had previously been documented for neurons, RTD2 does not compromise the morpho -functional features of astrocytes.